2009
DOI: 10.2165/11315200-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Elite Golf

Abstract: Elite golfers commonly use fitness and technical training to become more competitive. The aim of this paper was to review the literature regarding the relationships between elite golfers' playing results, technique and physique. The competitive outcome is a direct function of the score. The three golf statistical measures that show the strongest correlations to scoring average are greens in regulation (GIR), scrambling, and putts per GIR. However, more detailed game statistics are needed where the distances to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 41 publications
3
47
0
2
Order By: Relevance
“…The present study also confirmed that the mood of the golfers is unpredictable while performing the task [17,18]. For instance, the effectiveness of PIM training with PETTLEP imagery components helped to control the negative mood and increased the positive mood of the golfers.…”
Section: Discussionsupporting
confidence: 83%
“…The present study also confirmed that the mood of the golfers is unpredictable while performing the task [17,18]. For instance, the effectiveness of PIM training with PETTLEP imagery components helped to control the negative mood and increased the positive mood of the golfers.…”
Section: Discussionsupporting
confidence: 83%
“…Given its relative importance within the game of golf it is unsurprising that much research has focused on improving accuracy in golf putting (Hellstrom, 2009a). Requiring precise and accurate movements and often performed under conditions of high pressure, the golf putt is a skill particularly susceptible to breakdown (Gucciardi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In competitive golf, the player’s ability to hit the ball a long distance affects the score in a positive way [1], and research highlights the importance of driving distance in relation to golf performance [2]. Initial ball velocity is dependent on centeredness of impact, club head velocity (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies have included rotational tests or incorporated training exercises aimed to mimic the ballistic movements in the golf swing and they found marginal changes in CHS (1.5–1.6%) and in driving distance (4.3%) [16, 21]. Intervention studies using strength training in golf have received some criticism for a lack of research on skilled golfers and inclusion of control groups [1, 8]. The most common performance variable measured is CHS, however a review [8] found that ball speed was the driver performance variable most likely to increase from a strength training intervention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation